Are prions transported by plasma exosomes?. Issue 1 (August 2016) - Cervenakova, Larisa; Saá, Paula; Yakovleva, Oksana; Vasilyeva, Irina; de Castro, Jorge; Brown, Paul; Dodd, Roger
Abstract: Blood has been shown to contain disease-associated misfolded prion protein (PrP TSE ) in animals naturally and experimentally infected with various transmissible spongiform encephalopathy (TSE) agents, and in humans infected with variant Creutzfeldt–Jakob disease (vCJD). Recently, we have demonstrated PrP TSE in extracellular vesicle preparations (EVs) containing exosomes from plasma of mice infected with mouse-adapted vCJD by Protein Misfolding Cyclic Amplification (PMCA). Here we report the detection of PrP TSE by PMCA in EVs from plasma of mice infected with Fukuoka-1 (FU), an isolate from a Gerstmann–Sträussler–Scheinker disease patient. We used Tga20 transgenic mice that over-express mouse cellular prion protein, to assay by intracranial injections the level of infectivity in a FU-infected brain homogenate from wild-type mice (FU-BH), and in blood cellular components (BCC), consisting of red blood cells, white blood cells and platelets, plasma EVs, and plasma EVs subjected to multiple rounds of PMCA. Only FU-BH and plasma EVs from FU-infected mice subjected to PMCA that contained PrP TSE transmitted disease to Tga20 mice. Plasma EVs not subjected to PMCA and BCC from FU-infected mice failed to transmit disease. These findings confirm the high sensitivity of PMCA for PrP TSE detection in plasma EVs and the efficiency of this in vitro method to produce highly infectious prions. The results of our study encourage further research to define the role of EVs and, more specifically exosomes, as blood-borne carriers of PrP TSE .